Kvinnliga skogsmaskinförare i Sverige – rekrytering och nuläge - Karlsson, Linda Maria (SLU/School for Forest Management, 2016)
The purpose of this study is to find out how the Swedish forestry could increase the number of female forest machine operators. The sector is in a shortfall situation since the traditional recruitment groups are getting significantly smaller, groups such as young boys from the countryside. Other reasons to the shortfall are smaller youth groups, trends, urbanization, economic pressure, alone working, retirements and more. The females in the sector today only represent a small part of the workforce, and are looked upon as an unused asset. The forest sector works hard on many levels to increase the number of female machine operators. The study is based upon qualitative telephone interviews with eight women operating forest machines as a profession. The women interviewed are from different parts of Sweden and with differing experience. As a complement to the study an inquest concerning the amount of forest female machine operators as well as women studying to become forest machine operators today was completed. This inquest was followed through by asking schools as well as professional associations. The conclusions from the study are that the Swedish forestry should invest more to inform the public what this type of work is all about, especially the youth in the age span 13 to 16, who are about to decide what to study in upper secondary school. Another conclusion is that the attitudes towards women in the forest sector are for the most ppart positive and there is no problem for a woman to operate a forest machine!